Gravity Perspective of Trade Realignment: Assessing China's Engagement in West Africa. (September 2019) - Azu, Nnanna P.; Okezie, Benedette Nneka; Hirwa, Amatus
This article examines the impact of emerging West African trade partners—China and India with respect to the traditional trade partners. In this regard, we augmented the gravity model and used dummy to capture bilateral trade effects. This allowed trade to be represented from both sides of its occurrence—import and export—while also accounting for the percentage increase as well as the volume of trade. Applying poisson pseudo maximum likelihood (PPML) technique, we observed a growth in the coefficient of emerging trading partners concerning China in the import direction and India in the export direction, while that of the traditional trade partners remained positive but decreasing. Therefore, West Africa is witnessing a partial and imperfect realignment of trade with China, predominantly on import. As China continues to provide better prices and aids for trade, merchandise trade activities with the traditional partners may start to negatively impact when competing with emerging China.